Transparansi, Keamanan, dan Kepercayaan: Apa yang Mendorong Niat Mahasiswa untuk Berdonasi Melalui Platform Crowdfunding? - Nadya, Putri; Haris Riyaldi, Muhammad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study aims to analyze the influence of transparency and security on the interest of students to donate using a crowdfunding platform, with trust as a moderating variable. The sample used was 100 respondents who were selected using the proportional stratified random sampling technique. The data analysis techniques used are multiple linear regression analysis and moderated regression analysis. The results of the study show that transparency and security have a positive and significant impact on students' interest in donating. The trust variable is able to positively moderate the relationship between transparency, security, and students' interest in donating. It is hoped that the Kitabisa.com crowdfunding platform can maintain transparency and improve security in order to gain consumer trust and increase interest in donating.